2003
DOI: 10.13060/00380288.2003.39.1.06
|View full text |Cite
|
Sign up to set email alerts
|

Czech Folk Music in the 1960s-80s from the Point of View of the Sociology of Religion

Abstract: The article provides an in-depth functional analysis of Czech folk music from the 1960s to the 1980s from the viewpoint of the sociology of religion. In this period folk music played an important ideological and socio-political role in Czechoslovakia due to the values it embodied which made it strongly critical of the communist regime. The author attempts to explain that a significant part of these values were of religious (usually Christian, but also Oriental) origin, and they evolved specific symbolic univer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Czechs have long been suspicious about church-organised religion, but not about the 'neo-Durkheimian' forms of religiosity, transferring piety to ethnic, class or state entities [Taylor 2002: 78], and not about privatised religious matters. My recent research has shown that even in the period of communism many people searched for religion-like symbolic universes, which they found, for example, in what was expressed by so-called protest songs [Nešpor 2003]. intellectuals (L. Kunte, R. Máša, some of the so-called Catholic modernists) tried to establish a new religion, or initiated a certain revival of 'pure' Christianity [see Horyna and Pavlincová 1999: 197-223], while others actually succeeded in doing so (the founding fathers of Církev československá/Czechoslovak Church).…”
Section: The Historical Roots Of Czech Anti-clericalismmentioning
confidence: 99%
“…Czechs have long been suspicious about church-organised religion, but not about the 'neo-Durkheimian' forms of religiosity, transferring piety to ethnic, class or state entities [Taylor 2002: 78], and not about privatised religious matters. My recent research has shown that even in the period of communism many people searched for religion-like symbolic universes, which they found, for example, in what was expressed by so-called protest songs [Nešpor 2003]. intellectuals (L. Kunte, R. Máša, some of the so-called Catholic modernists) tried to establish a new religion, or initiated a certain revival of 'pure' Christianity [see Horyna and Pavlincová 1999: 197-223], while others actually succeeded in doing so (the founding fathers of Církev československá/Czechoslovak Church).…”
Section: The Historical Roots Of Czech Anti-clericalismmentioning
confidence: 99%
“…Folk singers may also act as leaders, gathering oppressed peoples and providing them with hope through the messages and values which they espouse. This is the effect found by Nespor (2003) in research on Czech folk music from the 1960s to the 1980s which criticised the communist regime. In Nigeria, people from the Yoruba cultural area, the most active sector of civil society, used theatre, oratory and folk music to criticise Structural Adjustment Programmes and challenge the military during the authoritarian regime from 1988 to 1999 (Olukotun, 2002).…”
Section: Positive Responses To Folk Musicmentioning
confidence: 82%
“…Folk singers may also act as leaders, gathering oppressed peoples and providing them with hope through the messages and values which they espouse. This is the effect found by Nespor (2003) in research on Czech folk music from the 1960s to the 1980s which criticised the communist regime. In Nigeria, people from the Yoruba cultural area, the most active sector of civil society, used theatre, oratory and folk music to criticise Structural Adjustment Programmes and challenge the military during the authoritarian regime from 1988 to 1999 (Olukotun, 2002).…”
Section: Positive Responses To Folk Musicmentioning
confidence: 82%